Dietary supplement use, impact on micronutrient intake of young german athletes - Braun, H.; Koehler, K.; Geyer, H.; Mester, J.; Thevis, M.; Schaenzer, W. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
It is widely accepted, that the use of Dietary Supplements (DS) does not compensate for an inadequate diet and DS use in young athletes should be discouraged (IOC Statement 2011). In contrast studies have shown a high prevalence of DS use in young athletes (Braun et al. 2009). In most studies, the prevalence of use was assessed, but little is known about dosage and nutrient intake from DS. Therefore, the aim of this study is to evaluate dietary intake, DS use and its impact on total nutrient intake of young athletes. Methods & Subjects: Between April and May 2011, 27 young athletes (age 13-18y) reported their diet using a validated 7-d food and activity record (Koehler et al. 2010). Energy intake and micronutrient intake was estimated based on the German food database (BLS II.3) using Ebispro Software. Athletes were asked to name all DS (e.g. company name, dosage pattern, frequency of use) used within the 7 days of food recording. Each DS was included into the food database to evaluate the diet with and without DS use. Results: We found 12 athletes (44%) using 16 different DS (15x vitamins and/or minerals, 1x protein powder enriched with vitamins/minerals). None of these athletes had any experience with individual nutrition counseling so far. Assuming that dietary micronutrient intake should be 100% RDA, this level was reached by all athletes only for copper and vitamin K. At least half of the group did not reach the RDA for vitamin D (n=11 athletes), folic acid (n=11), iron, vitamin B12, pantothenic acid, and vitamin A (n=6 each). Micronutrient intake was improved above 100% RDA by DS use only for vitamin D (n=2), vitamin C (n=1) and iron (n=3). Furthermore, DS use increased micronutrient intake towards tolerable upper intake levels for iron (n=3), magnesium (n=3), zink (n=2), and vitamin B6 (n=1). Discussion: In the present study, dietary intake of young athletes did not meet the RDA for selected micronutrients. Supplementation with vitamins and minerals did increase micronutrient intake (> 100% RDA) only for few athletes and nutrients. Some athletes took micronutrients leading to intakes higher than the suggested upper intake levels. Based on these preliminary data, the use of DS did not enhance micronutrient intake in young athletes substantially. Therefore, we suggest that young athletes need more information on optimizing their diet, but also more information on a wise use of dietary supplements.